ULAMA DALAM KONSTITUSI NEGARA IMAMAH - Usman, Usman (Islamuna: Jurnal Studi Islam, 2017)
’Ulama are the inheritors of the Prophet’s struggle in the present, so they have a very significant role in the life of the state and society in a country. One of the modern political events that occurred was the 1979 revolution in Iran led by the ’Ulama, which gave birth to a new constitution, namely the concept of Imamah, the Wilayah al-faqih and maraja’i taqlid are very important. In this new constitution, what is the role of ’Ulama as the main reference in government.